Credibility of CSR and Sustainability Reporting in India: An Empirical Study of Economic and Philanthropic CSR Practices in Public and Private Sector Organizations - Chouhan, Vineet; Goswami, Shubham (Copernican Journal of Finance & Accounting, 2026)
Parameters such as readability, adherence to reporting guidelines, data quality, and stakeholder dialogue are considered to assess the credibility of information in a company’s annual and sustainability reports. An examination of the reliability aspect of Corporate Social Responsibility (CSR) and sustainability reports (SR) from specific companies reveals that nearly all of them present information in a clear and comprehensible format, and adhere to fundamental reporting principles, such as providing details about the time period covered. CSR reports include details about the constraints and the specific demographic the organization aims to reach. The data for the study is gathered from 280 respondents who are working as the finance/Accounting manager or financial professionals i.e., CA (Chartered Accountant), CS (Company Secretary) or (Management Accountant) ICMAI using structured questionnaire with close ended questions, who are working in the Public and private sector in India. The same is analysed with the one sample t test and multiple regression tools with the SPSS software.The results revealed that two variables Economic CSR played a key role in improving the effectiveness of policies and operational measures of CSR and Philanthropic are effectively predicting the good CSR policies and procedure in public and private sector organisation.